1986
DOI: 10.1079/bjn19860058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fibre isolates on gastric secretion, acidity and emptying

Abstract: 1. In six volunteers, the effect of intragastric administration of different water-soluble chemical isolates of dietary fibre on gastric secretion, acidity and emptying was studied.2. At 30 min after administration of the test meals, the stomach contents were completely aspirated and the volume, pH, phenol red concentration, totai titratable acidity and different electrolytes were measured.3. Compared with the control meal, the pH and unionized (combined) hydrogen concentrations were significantly higher (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…An influence of increased viscosity in a sample or pH changes in gastric acid resulting from the presence of polysaccharides on gastric digestion was observed by other researchers in animals [26–30]. We obtained partial protection when pectin was added to the purified kiwi TLP in vitro .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…An influence of increased viscosity in a sample or pH changes in gastric acid resulting from the presence of polysaccharides on gastric digestion was observed by other researchers in animals [26–30]. We obtained partial protection when pectin was added to the purified kiwi TLP in vitro .…”
Section: Discussionsupporting
confidence: 66%
“…We applied the same standardized assay to study the susceptibility of the proteins tested in our study to the pepsin digestion in the presence of fruit matrix, pectin and viscosity phenomena due to a high sugar content with the same purpose. An influence of increased viscosity in a sample or pH changes in gastric acid resulting from the presence of polysaccharides on gastric digestion was observed by other researchers in animals [26][27][28][29][30]. We obtained partial protection when pectin was added to the purified kiwi TLP in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…The viscosity of the formulation in the present study is higher than that of the proprietary formulation at slurry concentration ranging from 1-5%. Its consistency is not affected by variations in acidity or alkalinity of the aqueous suspension exhibiting buffering action (Table 6), which indicated its beneficial effect in controlling acidity and similar complications of the digestive tract [33]. The formulation or the bran can be mixed with other traditional foods such as chapathi or bread to enhance the dietary fibre content.…”
Section: Resultsmentioning
confidence: 98%
“…This has been clearly shown for liquid meals. In fact, it has been repeatedly shown that pectin and guar gum delay the gastric emptying of glucose solutions, reducing the glycaemic response, [8][9][10][11][12][13] and that this delay is mediated, at least in short term experiments, by the increase in viscosity of gastric contents.14 15 The relation between postprandial glycaemia and gastric emptying is more complex when liquid starch is ingested, as other factors, such as the susceptibility to ao-amylase,16 play a part. The effect of fibre on solid meals is even more controversial.…”
Section: Introductionmentioning
confidence: 99%